A primary culture method for the easy, efficient, and effective acquisition of oligodendrocyte lineage cells from neonatal rodent brains - Hanki Kim; Bum Jun Kim; Seungyon Koh; Hyo Jin Cho; Xuelian Jin; Byung Gon Kim; Jun Young Choi (Heliyon, 2024)
Oligodendrocytes (OL) are myelin-forming glial cells in the central nervous system. In vitro primary OL culture models offer the benefit of a more readily controlled environment that facilitates the examination of diverse OL stages and their intricate dynamics. Although conventional methods for primary OL culture exist, their performance in terms of simplicity and efficiency can be improved. Here, we introduce a novel method for primary OL culture, namely the E3 (easy, efficient, and effective) method, which greatly improves the simplicity and efficiency of the primary OL culture procedure using neonatal rodent brains. We also provided the optimal media composition for the augmentation of oligodendrocyte progenitor cell (OPC) proliferation and more robust maturation into myelin-forming OLs. Overall, E3 offers an undemanding method for obtaining primary OLs with high yield and quality. Alongside its value as a practical tool, in vitro characteristics of the OL lineage additionally identified during the development of the E3 method have implications for advancing research on OL physiology and pathophysiology.